2012
DOI: 10.1044/1059-0889(2012/12-0002)
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Speech Recognition and Loudness Perception With the Desired Sensation Level v5 Quiet and Noise Prescriptions

Abstract: Average-level consonant recognition in quiet was preserved and aversive loudness was alleviated by the Noise prescription relative to the quiet prescription, which suggests that the DSL v5 Noise prescription may be an effective approach to managing the nonquiet listening needs of children with hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 44 publications
7
29
0
Order By: Relevance
“…Comparisons are further complicated by the fact that updated versions of each algorithm (DSL v.5 and NAL-NL2) have been developed and are used clinically by pediatric audiologists. Despites these developments, Crukley & Scollie (2012) reported similar speech recognition outcomes for DSL v.5 as were reported for DSL 4.1 in quiet. This trend reflects the fact that changes to pediatric prescriptive formulae are based on evidence and would not be likely to result in significant changes in audibility or speech understanding.…”
Section: Discussionsupporting
confidence: 58%
“…Comparisons are further complicated by the fact that updated versions of each algorithm (DSL v.5 and NAL-NL2) have been developed and are used clinically by pediatric audiologists. Despites these developments, Crukley & Scollie (2012) reported similar speech recognition outcomes for DSL v.5 as were reported for DSL 4.1 in quiet. This trend reflects the fact that changes to pediatric prescriptive formulae are based on evidence and would not be likely to result in significant changes in audibility or speech understanding.…”
Section: Discussionsupporting
confidence: 58%
“…However, this approach was necessary, in our instrumentation, because we wanted to offer participants the ability to make paired comparison judgements across hearing aids with rapid switching between pairs of stimuli. Also, some studies have shown that combining ANR with directionality and/or alternative hearing aid prescriptions may improve outcomes at least for loudness, although this may be limited when large vents are used (Crukley and Scollie, 2012;Magnusson et al, 2013). Finally, we did not assess the real-world outcomes associated with the use of these ANR processors, the impact of testing at other test levels, or the use of ANR in combination with other hearing aid features.…”
Section: General Discussion and Protocol Developmentmentioning
confidence: 99%
“…However, we know that children and infants experience a wide range of auditory environments in their daily lives. Many of these environments include high and varying levels of speech, background noise, and/or reverberation (Crukley et al, 2011), and may be louder than desired for children and infants who wear hearing aids even if loudness is normalized on formal loudness rating tasks (Ching et al, 2010;Scollie et al, 2010a;2010b;Crukley and Scollie, 2012). In addition, some children (and adults) experience significantly higher loudness perception than do others with similar hearing losses and similar amplification.…”
Section: Overview Of Automatic Noise Reduction Technology and Effectsmentioning
confidence: 99%
“…Nevertheless, the findings in this current study cannot be generalized to listening in noise. This is because the DSL v5 prescription includes a noise program target with less gain than the quiet program (Scollie et al, 2005;Crukley and Scollie, 2012). For future investigations, it will be necessary to examine the impact of choice of prescriptions on speech intelligibility in noise and loudness for children fit with the noise program of DSL v5, and the updated version of the NAL prescription, NAL-NL2 (Dillon et al, 2011).…”
Section: Limitationsmentioning
confidence: 99%